C2 Segmental-Type Vertebral Artery Diagnosed Using Computed Tomographic Angiography - Kim, Myoung Soo (J Korean Neurosurg Soc, 2018)
OBJECTIVE: Sometimes a vertebral artery (VA) enters the spinal canal via the C1–2 intervertebral space, a variation regarded as a C2 segmental-type VA. This paper describes the anatomy of the C2 segmental-type VA and reviews its clinical importance. METHODS: Between March 2014 and November 2015, 3386 patients underwent computed tomographic angiography. I identified C2 segmental-type VAs, associated vascular variation, the origin of ipsilateral posterior inferior cerebellar arteries (PICAs), and the clinical symptoms associated with C2 segmental-type VAs. The origin of an ipsilateral PICA is divided into 5 types. A type 1 PICA originates from ipsilateral VAs coursing suboccipitally (IVASO), a type 2 originates from ipsilateral proximal C2 segmental-type VAs, a type 3 originates from ipsilateral distal C2 segmental-type VAs. For type 4, the PICA does not originate from an ipsilateral VA. For type 5, the PICA is the terminal end of an ipsilateral C2 segmental-type VA. RESULTS: One hundred thirteen patients had 121 C2 segmental-type VAs; 47 were associated with an IVASO, and 74 were not. Four type 1, 13 type 2, 60 type 3, 42 type 4, and two type 5 PICAs were identified. Only one patient showed symptoms associated with a C2 segmental-type VA, being a 71-year-old man presenting with a C2 segmental-type VA infarction. CONCLUSION: For C2 segmental-type VAs, the ipsilateral IVASO and origin of the PICA are important for predicting the outcome of this type of VA infarction.